Study Of Vaginal Microflora In Cases Of Preterm Prelabour Rupture (PPROM): A Case Control Study - Mahaseth, Binod Kumar; B.C., Durga (Journal of Nepalgunj Medical College, 2019)
Background: Globally, Preterm delivery is a major contributory factor for early neonatal death. Till date definite causative factor for preterm labour has not been proven. However, the genital tract infection is considered to be the contributory factors for PPROM.Method: This case control study was conducted at Nepalgunj Medical College Teaching Hospital, Kohalpur. 100 cases enrolled in the study were divided into two groups; group A consisted of 50 cases with PPROM; and in group B 50 cases were included cases without PPROM who came to routine antenatal check-up in ANC (antenatal care) clinic. The high vaginal swab was taken from the upper one-third of the posterior wall of the vagina and sent for culture and sensitivity in all cases.Results: In group A (with PPROM)74% of cases were culture positive and the commonest organism was E. coli which was isolated in 40% (20/50). In group B (without PROM) 28% of cases had culture positive, and again the commonest organism was E. coli isolated in 14 % cases (7/50). This present study showed that E. coli was most sensitive to amoxyclav and staphylococcus epidermis was most sensitive to nitrofurantoin. Ceftriaxone was found to be most effective in mixed infections.Conclusions: The genital tract infections in PPROM group was very high (+ve) culture in 74% in comparison to the non PPROM group where genital tract swab showed growth in only 28% (p-value 0.001). The lower genital tract infection has been considered as one of the potent cause of PPROM, so it is advised that a vaginal swab should be routinely obtained in the ANC clinic for culture and sensitivity. An appropriate antibiotic should be started in culture positive cases.